Socio-Cultural Adaptation and Integration of Migrants as Tool of State Migration Policy in Soviet Period - T. A. Bazhan (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Russian migration policy is facing a number of problems, whose effective solution has not been found yet. They include the absence of infrastructure for social and cultural adaptation and integration of migrants and high level of illegal migration. The system of organized drawing-in workers-migrants has not been developed. To resolve these problems it would be useful to analyze the experience of the soviet period, when complicated migration problems were successfully settled. A system of steps aimed at assisting socio-cultural adaptation and integration of internal migrants was promoted by involvement of the population in their solution. The present article analyzes specific features and mechanisms of state migration policy of the soviet period, which supported the needs of economy in labour, helped populate the remote areas of the country and create conditions for the development of human capital. State policy in this sphere was planned and successive: it staked at internal labour migration; migration flows were regulated; state was interested in the development of industrial, agricultural and cultural potential of territories, where migrants arrived. Critical study of the experience of migrants’ adaptation and integration in this period, identifying mechanisms, which can work in current conditions would allow us to optimize today’s migration policy and practice of its pursuing.